Application of phase-metric compensation method for geoelectric control of near-surface geodynamic processes - Kuzichkin O. R.; Vasilyev G. S.; Grecheneva A. V.; Mikhaleva E. V.; Baknin M. D.; Surzhik D. I. (Bulletin of Electrical Engineering and Informatics, 2020)
This work is devoted to the application of the compensation method of geoelectric control using the field phase characteristics for the detection and localization of geodynamic processes on example of the development of the karst-suffusion cavity. High noise immunity of the phase-metric registration method of geoelectric signals in comparison with amplitude parameters of the anomalous components of electromagnetic field, usually used to analyze the results of observations, is noted. A formalized approach to the use of phase characteristics of the field for the interpretation of monitoring data and associated problem of geodynamic processes localization is developed. In the framework of this approach, the section parameters are proposed to determine by the minimum sum of weighted mean square interpretation error and regularizing functional containing a priori information about the geoelectric section. To check localization possibility of the spherical karst-suffusion cavity, simulation of the amplitude and phase anomalous components of the field potential, as well as the standard error of heterogeneity localization, when moving the sphere center along the installation profile, is carried out. Simulation has shown a good potential differentiation from the inhomogeneity position, the highest accuracy of localization is achieved with combined use of amplitude and phase field components in the problem of inhomogeneity localization.